DESIGNING THE METHODICAL SYSTEM OF THE TEACHING PROCESS OF COMPUTER GRAPHICS FOR THE SPECIALTY OF ENGINEER-BUILDER - Islomovna, Mamurova Feruza; Isomjonovna, Ruzieva Dilnoza; Islоm, Mamurov; Sharifovn, Khodjaeva Nodira; Islomovna, Mamurova Dilfuza (The journal of contemporary issues in business and government, 2021)
The focus on the effectiveness of teaching computer graphics in the developed countries of the world is growing due to the importance of making significant changes in the development and globalization of computer technology, determining the development of advanced technologies. Today, the visualization of computer graphics education in the world's leading universities, the creation of favorable conditions for the training of specialists in the field, such as CAD master, animator, the development of design culture of future professionals play an important role in the education of sustainable development.